1983
DOI: 10.1002/art.1780260208
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of sera from patients with scleroderma

Abstract: Sera from patients with progressive systemic sclerosis were compared with sera from normal individuals and from patients with other connective tissue diseases for cytotoxic effects on cultured human cells. More than 40% of the sera from patients with active progressive systemic sclerosis were cytotoxic by several criteria for pulmonary arterial or umbilical venous endothelial cells, foreskin fibroblasts, and neuroblastoma cells. Cytotoxic sera caused morphologic changes, uptake of trypan blue dye, and a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This led to the hypothesis that a serum factor might induce vascular damage. Studies in the 1980s focused on various effects of SSc sera on cell cultures,59 60 61 62 63 64 65 and the observed prevalence of SSc sera cytotoxicity ranged from 19% to 75%. Some of these studies61 62 64 demonstrated antibody-dependent cell cytotoxicity mediated by SSc sera on various EC substrates, a mechanism also described in SLE66 and in WG 67.…”
Section: Pathogenic Role Of Aeca In Sscmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the hypothesis that a serum factor might induce vascular damage. Studies in the 1980s focused on various effects of SSc sera on cell cultures,59 60 61 62 63 64 65 and the observed prevalence of SSc sera cytotoxicity ranged from 19% to 75%. Some of these studies61 62 64 demonstrated antibody-dependent cell cytotoxicity mediated by SSc sera on various EC substrates, a mechanism also described in SLE66 and in WG 67.…”
Section: Pathogenic Role Of Aeca In Sscmentioning
confidence: 99%
“…Some authors assumed the cytotoxic factor in SSc serum to be a protease 59 68. This hypothesis remains interesting because further research69 demonstrated the presence of a 60 kDa granzyme in SSc sera, inducing profound EC growth inhibition while having a mitogenic effect on fibroblasts.…”
Section: Pathogenic Role Of Aeca In Sscmentioning
confidence: 99%
“…Since then these antibodies have been described in a variety of connective tissue disease (Shingu & Hurd, 1981;Cohen, Johnson & Hurd, 1983;LeRoux et al, 1986;Baguley & Hughes, 1987;Hashemi, Smith & Izaguirre, 1987;Rosenbaum et al, 1988) and in association with vasculitis (Leung et al, 1986a(Leung et al, , 1986bBrasile et al, 1989;Heurkens et al, 1989;Ferraro et ai, 1990). Work in our laboratory and those of several other authors has shown that binding of AECA to endothelial cells is mediated by the F(ab')2 portion and not the Fc portion (Hashemi et al, 1987;Rosenbaum et al, 1988;Baguley & Hughes, 1989;Heurkens et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The activity was disease specific in some reports, while other reports described its presence in a small number of patients with other connective tissue diseases. The activity was reported to be the size of albumin, 40-SO kD in one report [68], as well as a SO00 dalton fraction in another study [70]. Some of the apparent confusion regarding endothelial cytotoxicity may involve methodologic differences, source of endothelial cells, and patient selection.…”
Section: Circulating Endothelial Cytotoxicitymentioning
confidence: 99%